2012
DOI: 10.1103/physrevlett.108.246401
|View full text |Cite
|
Sign up to set email alerts
|

Kondo Screening and Magnetism at Interfaces

Abstract: The nature of magnetic order and transport properties near surfaces is a topic of great current interest. Here we model metal-insulator interfaces with a multilayer system governed by a tight-binding Hamiltonian in which the interaction is nonzero on one set of adjacent planes and zero on another. As the interface hybridization is tuned, magnetic and metallic properties undergo an evolution that reflects the competition between antiferromagnetism and (Kondo) singlet formation in a scenario similar to that occu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
2
14
0
Order By: Relevance
“…6(a) shows the nontrivial peak of the penetration depth, whose position is consistent with the hybridization strength V where S AF reaches its minimum. This behavior of S AF (L) is qualitatively similar to the multilayer metal-insulator interface in the three-dimensional Hubbard model, 20 and can be attributed to singlet formation at the metal-insulator interface, which both suppresses S AF (L = 1) and also leaves the remaining lines L > 1 decoupled from the metal.…”
Section: Effect Of Variation Of Interface Hoppingmentioning
confidence: 54%
See 1 more Smart Citation
“…6(a) shows the nontrivial peak of the penetration depth, whose position is consistent with the hybridization strength V where S AF reaches its minimum. This behavior of S AF (L) is qualitatively similar to the multilayer metal-insulator interface in the three-dimensional Hubbard model, 20 and can be attributed to singlet formation at the metal-insulator interface, which both suppresses S AF (L = 1) and also leaves the remaining lines L > 1 decoupled from the metal.…”
Section: Effect Of Variation Of Interface Hoppingmentioning
confidence: 54%
“…This enables us, for example, to evaluate the penetration depth across the boundary, since the interface effects have sufficient room to heal before the lattice edge. The behavior of the Hubbard model across a planar interface in a 3D material on systems of smaller linear extent has been explored by Euverte et al 20 The key finding is that up to an interface hopping V , which is on the order of the bulk hybridization t, the effects of the interface can extend well past the two layers immediately at the interface. That is, the interface affects properties 3-4 layers deep on both the strongly and weakly correlated sides of the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Unusual properties have been discovered at these interfaces, such as strongly confined metallic phases 13 , magnetism 14 , and superconductivity 15 to name a few. The occurrence of a metallic interface through electronic rearrangement is one of the intriguing features of the BI/MI heterostructures [16][17][18][19][20][21] . Naturally we may ask how the situation is modified when the band insulator is replaced by a topological insulator (TI).…”
Section: Pacs Numbersmentioning
confidence: 99%
“…A significant number of theoretical studies on the proximity effects of electron-electron interaction in layered systems have been carried out. Such studies include proximity effects in Hubbard layers [10][11][12][13][14][15][16][17][18] , FalicovKimball layers 19 or f -electron superlattices 20,21 . Zenia et al 12 demonstrated that a Mott insulator transforms to a "fragile" Fermi liquid if sandwiched between metallic leads.…”
Section: Introductionmentioning
confidence: 99%